Examining the influence of copper recycling on prospective resource supply and carbon emission reduction - Jinhui Li; Disna Eheliyagoda; Yong Geng; Zhiming Yang; Xianlai Zeng (Fundamental Research)
Copper is an economic and strategic metal consumed and produced in many nations. Previous studies of future copper demand and supply have revealed some deficiencies at the macro level. To minimize these gaps, we present here a comprehensive recycling scenario to examine the future copper sustainability for more than 50 countries by 2100. End-of-life metal recycling optimization can be a transparent, flexible and broadly applicable solution, coupled with circular economy strategies to reduce the supply of such metals and related environmental risks. Substantial recycling (estimated at 40 to 65 percent) would be more conducive to reducing primary demand in regions with large populations and rapid industrial growth. Although Latin America and Caribbean, Africa and Oceania can be identified as regions with low demand and recycling intentions by 2100, carbon emissions in Latin America will peak at 70 million tons by 2050 owing to concentrated primary copper production. In order to fully realize recycling targets, more efforts should be made to formulate policies and regulations for the copper industry, systematically scrap collection, and innovate effective technologies.